2001
DOI: 10.1590/s0004-282x2001000100018
|View full text |Cite
|
Sign up to set email alerts
|

Esclerose múltipla: correlação clínico-laboratorial

Abstract: RESUMO -Aspectos clínicos e demográficos de 86 pacientes com o diagnóstico de esclerose múltipla (EM) forma clinicamente definida foram comparados aos achados do líquido cefalorraqueano. Do grupo total 30% encontrava-se em surto, 41% em remissão e 29% na forma crônica progressiva. Os pacientes com a forma crônica progressiva apresentavam índice de IgG sugestivo de imunoliberação intratecal em 76% dos casos, enquanto que aumento deste parâmetro foi observado em apenas 46% e 49%, das formas em surto e remissão, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
1
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
2
1
3
Order By: Relevance
“…The frequency of OCB found in this study is low in comparison with both the prevalence observed in European and North-America MS patients and other previous Brazilian studies which found a frequency of 85% 17 and 91% 18 . However, this low rate is similar to that observed in other regions of the world (Table 4).…”
Section: Resultscontrasting
confidence: 92%
“…The frequency of OCB found in this study is low in comparison with both the prevalence observed in European and North-America MS patients and other previous Brazilian studies which found a frequency of 85% 17 and 91% 18 . However, this low rate is similar to that observed in other regions of the world (Table 4).…”
Section: Resultscontrasting
confidence: 92%
“…The main symptoms are fatigue, pain, spasticity, sensitive and motor dysfunctions, sexual and bladder dysfunctions, as well as cognitive impairments, and signs of depression. Less common are bowel dysfunction, paroxysmal symptoms, and symptoms pertinent to bipolar disorder (Campston, 2004;Feyes et al, 2004;Mendes, Tilbery, Balsimelli, Moreira, & Barão-Cruz, 2003;Mendes, Tilbery, & Felipe, 2000;Minguetti, 2001;Puccioni-Soher, Lavrado, Bastos, Brandão, & Papaiz-Alvarenga, 2001;Reder, 2004;Sadiq & Miller, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the diagnosis is determined by laboratory analysis, exams of somatosensory evoked potentials, and magnetic resonance imaging Poser & Brinar, 2004;Puccioni-Soher et al, 2001;Sadovnick, 2004;Sastre-Garriga et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As formas menos comuns são a progressiva primária e a progressiva em surtos, com comprometimentos contínuos desde o início da doença (40-60 anos). Somente a forma progressiva em surtos tem discreta remissão, com ou sem alguma recuperação (COMITÊ BRASILEIRO DE TRATAMENTO E PESQUISA DA ESCLEROSE MÚLTIPLA, 2005a, 2005bFERREIRA et al, 2004;PUCCIONI-SOHLER et al, 2001;SÁ, 2004).…”
Section: Introductionunclassified